REINTEPRETASI PENGKLASIFIKASIAN HADIS (MENEROPONG PROBLEMATIKA DAN SOLUSI HADIS ERA KONTEMPORER) - Muttaqin, Muhammad Ngizzul (IAIN Kediri, 2019)
As the second source of Islamic teachings after the Qur?an, the Hadith has an important position towards the development of Islamic teachings. The search of the history of the Hadith certainly has very long twists and turns, the era of the Prophet Muhammad, Companions, Tabi?in to the Muhadithin. The dynamics of thedevelopment of the Hadith is also accompanied by the development of the ulumul hadith, one of the aims of the existence of the ulumul hadith is to look for the authenticity of a Hadith, until the theory of the classification of Hadith emerges in terms of the quality or quantity of the Hadith. However, in line with the development of this contemporary era, the Hadith experiences a problem when it must adapt to the conditions and socioculture of society. Historical aspects, authority, reinterpretation, authenticity to methodology are considered to be separate problems experienced by this second source of Islamic teachings in the contemporary era. As a literature study and literature study, this paper attempts to reinterpret the classification of Hadith and reveal the problems of the Hadith in the contemporary era, so as to produce a solution to the continuity of the Hadith in the contemporary era.Keywords: Classification of Hadith; Problematics; Solutions; Contemporary Era.